Assessment of electronic disease early warning system for improved disease surveillance and outbreak response in Yemen - Dureab, Fekri; Beiersmann, Claudia; Jahn, Albrecht (BMC public health, 2020)
Diseases Surveillance is a continuous process of data collection, analysis interpretation and dissemination of information for swift public health action. Recent advances in health informatics have led to the implementation of electronic tools to facilitate such critical disease surveillance processes. This study aimed to assess the performance of the national electronic Disease Early Warning System in Yemen (eDEWS) using system attributes: data quality, timeliness, stability, simplicity, predictive value positive, sensitivity, acceptability, flexibility, and representativeness, based on the Centres for Disease Control & Prevention (US CDC) standard indicators.
Gesehen am 06.05.2022